2008
DOI: 10.1161/atvbaha.108.162735
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Zinc in Human Atherosclerotic Lesions Correlates With Calcium Levels But Does Not Protect Against Protein Oxidation

Abstract: Objective-Oxidized lipids and proteins, as well as decreased antioxidant levels, have been detected in human atherosclerotic lesions, with oxidation catalyzed by iron and copper postulated to contribute to lesion development. Zinc has been postulated to displace iron from critical sites and thereby protect against damage. In this study, metal ion and protein oxidation levels were quantified in human carotid and abdominal artery specimens containing early-to-advanced lesions, to determine whether zinc concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
2
26
1
4
Order By: Relevance
“…Existing data are contradictory regarding the negative or protective effects of zinc in the development of atherosclerosis [22][23][24]. In study of Stadler et al [25], elevated levels of zinc (about 6-fold) were detected in advanced lesions compared to healthy tissue or early lesions. They found the highly-significant positive correlations between zinc and calcium in samples of carotid endarterectomy (r=0.895; P=0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Existing data are contradictory regarding the negative or protective effects of zinc in the development of atherosclerosis [22][23][24]. In study of Stadler et al [25], elevated levels of zinc (about 6-fold) were detected in advanced lesions compared to healthy tissue or early lesions. They found the highly-significant positive correlations between zinc and calcium in samples of carotid endarterectomy (r=0.895; P=0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained from these groups were compared to control subjects without significant atherosclerotic changes in carotid artery. Previous studies have reported that advanced atherosclerotic lesions have higher metal ion levels than initial lesions or healthy tissue (11,21,22).…”
Section: Discussionmentioning
confidence: 95%
“…[18] объясняли повышение уровня цинка как защитный эффект при атеросклерозе. Так, цинк может участвовать в механизме повышения стабильности АСБ, путем связывания с компонентами матрикса.…”
Section: Discussionunclassified